Sexuality and pathological specialization In Sphaerotheca fuliginea - KABITARANI, A. (Indian Phytopathology, 2002)
Five conidial isolates of Sphaerotheca fuliginea from Cucurbita moschata were mated on detached whole leaf cultures. Cleistothecia formed in eight compatible matings at the meeting point of the two cultures. Cleistothecia never developed in single cultures. Single conidial isolateds from Luffa cylindrica, Cucurbita pepo, C. moschata, Lagenaria siceraria, L. siceraria var. clavata and Sechium edule were cross-inoculated to either host. Isolate from L. cylindrica was virulent to C. moschata, C. pepo and its own host. Isolates from other host species infected each host species except L. cylindrica. It is concluded that S.fuliginea is heterothallic and it occurs in two pathological races in Manipur. Significance of these conclusions in breeding resistant variety is discussed.